2023
DOI: 10.1177/01939459231182495
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Experienced by Perinatal Women with Opioid Dependency in the United States: A Qualitative Meta-Synthesis

Abstract: Stigma is a barrier to accessing care and treatment for perinatal women with pain and opioid dependency, resulting in increased maternal/neonatal morbidity and mortality, prolonged neonatal hospitalizations, and increased healthcare-related costs. This theory-generating qualitative meta-synthesis includes 18 qualitative research reports and describes the stigma-related experiences of perinatal women with opioid dependency. A model emerged consisting of cyclical yet pivotal care points, facilitators/deterrents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(309 reference statements)
0
3
0
Order By: Relevance
“…We therefore measured intimate partner or family violence (IPFV) during or 12 months before pregnancy by one’s husband, current or ex-partner, or another family member. Prior studies have shown that some physical and mental health conditions (eg, excess body weight and behavioral health disorders) carry stigmas that negatively shape health care professionals’ care and attitudes towards patients . We measured obesity (body mass index ≥30 [calculated as weight in kilograms divided by height in meters squared]) prior to pregnancy and self-reported diagnosis of the following conditions before or during pregnancy: chronic medical conditions (asthma, diabetes, or hypertension), substance use disorder (SUD) or addiction (excluding smoking or tobacco use), and mood disorders (depression, anxiety, or another mood disorder).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore measured intimate partner or family violence (IPFV) during or 12 months before pregnancy by one’s husband, current or ex-partner, or another family member. Prior studies have shown that some physical and mental health conditions (eg, excess body weight and behavioral health disorders) carry stigmas that negatively shape health care professionals’ care and attitudes towards patients . We measured obesity (body mass index ≥30 [calculated as weight in kilograms divided by height in meters squared]) prior to pregnancy and self-reported diagnosis of the following conditions before or during pregnancy: chronic medical conditions (asthma, diabetes, or hypertension), substance use disorder (SUD) or addiction (excluding smoking or tobacco use), and mood disorders (depression, anxiety, or another mood disorder).…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant women with OUDs often lack information or receive misinformation about OUD treatment and its impact on themselves and their babies [ 10 ]. A lack of adequate communication, breakdown in communication, or miscommunication experienced by pregnant women with opioid use disorders worsens perceptions of stigma from clinicians [ 11 ]. Therefore, the intentional education of patients about treatment options may reduce misinformation and stigma and may facilitate shared decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, breastfeeding rates in this vulnerable group are lower than the general population, even though they intend to establish and continue breastfeeding beyond the first few weeks 2,10. Clinicians and scholars recognize that women on OMT may experience barriers to breastfeeding beyond those of the general population 11-13. Several studies have found factors that prevent successful breastfeeding in women on OMT, including inaccurate information, misconceptions, and lack of support from providers and nurses 14-16.…”
mentioning
confidence: 99%